2005
DOI: 10.1136/oem.2004.017798
|View full text |Cite
|
Sign up to set email alerts
|

Identifying public water facilities with low spatial variability of disinfection by-products for epidemiological investigations

Abstract: Background and Aims: Epidemiological studies of disinfection by-products (DBPs) and reproductive outcomes have been hampered by misclassification of exposure. In most epidemiological studies conducted to date, all persons living within the boundaries of a water distribution system have been assigned a common exposure value based on facility-wide averages of trihalomethane (THM) concentrations. Since THMs do not develop uniformly throughout a distribution system, assignment of facility-wide averages may be inap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…All THM species were higher during summer, except for TCM, resulting in the absence of a season effect on the sum of the four THM species (total THM). Inevitably, certain studies showed higher total THM levels in tap water during summer Toroz and Uyak, 2005;Wei et al, 2010), where THM levels were higher either (i) in late summer (Villanueva et al, 2007;Symanski et al, 2004;Hinckley et al, 2005;Porter et al, 2005), or (ii) in late spring to early summer (Lewis et al, 2006). Keegan et al (2001) reported no seasonal effect on water total THM levels, corroborating our results.…”
Section: Between-area (Ba) Asupporting
confidence: 93%
“…All THM species were higher during summer, except for TCM, resulting in the absence of a season effect on the sum of the four THM species (total THM). Inevitably, certain studies showed higher total THM levels in tap water during summer Toroz and Uyak, 2005;Wei et al, 2010), where THM levels were higher either (i) in late summer (Villanueva et al, 2007;Symanski et al, 2004;Hinckley et al, 2005;Porter et al, 2005), or (ii) in late spring to early summer (Lewis et al, 2006). Keegan et al (2001) reported no seasonal effect on water total THM levels, corroborating our results.…”
Section: Between-area (Ba) Asupporting
confidence: 93%
“…Temporal analysis of monthly mean concentrations of regulated THMs and HAAs measured at residential locations in this study suggest that May and June are high months of DBP formation in this system, which is consistent with other surface water systems with similar seasonal patterns of rainfall [14,43,44,45,46,47]. Treatment stations A, B, and D show high mean monthly concentrations in May (June in some cases, e.g., THMs in station D and HAAs in stations B and D).…”
Section: Discussionsupporting
confidence: 88%
“…We recognize that the full extent of spatial variability may not be captured by existing DBP sample locations in some PWSs and that other approaches for quantifying the degree of spatial variability should be considered for different DBP metrics. 38 Nevertheless, our THMBr results seem robust to the impact of spatial variability in aggregated exposure measures.…”
Section: Discussionmentioning
confidence: 62%